Siphoninus finitimus (Hemiptera: Aleyrodidae), "olive whitefly" in Arica-Chile - Bobadilla Guzman, Dante; Cerda Hernandez, Carolina; Salvatierra Martínez, Ricardo; Sepúlveda Chavera, Germán F. (Revista de la Facultad de Ciencias Agrarias UNCuyo, 2022)
In this note are given background on the morphometric differences, in the genitalia of adults and the puparium of aleyrodidae populations associated with olive, pear and pomegranate in the region of Arica-Parinacota, Chile. The significant differences (p < 0.01) found in the dimension, and in the morphology of the structures studied between the different populations of whitelfly that attack to olive trees with regard to the pear and the pomegranate allow to establish that in Arica the whitefly of the olive tree is Siphoninus finitimus Silvestri and that S. phillyreae, it is associated with pear and pomegranate.